Scaling up biofortified crops and foods for healthier, inclusive, and resilient food systems: Calls to action for the UN Food Systems and Tokyo Nutrition for Growth Summits - HarvestPlus (International Food Policy Research Institute, 2021)
Addressing hidden hunger with nutrient-dense staple crops—developed through the process of biofortification—has gained considerable traction in low- and middle-income countries since the first varieties were released to farmers 16 years ago. This proven, practical, cost-efficient, and complementary malnutrition response for smallholder farming families and other low-resource populations is ready for rapid scale up to help achieve global development objectives. This brief summarizes the benefits and impact of biofortified crops and foods, and recommends commitments by key stakeholders to help catalyze scale up.